Chagas Disease in Pregnant Women in the Peruvian Amazon Basin. Cross-Sectional Study - Ramos-Rincón, José-Manuel; Ortiz-Martínez, Sonia; Vásquez-Chasnamote, María-Esteyner; Gamboa-Paredes, Olga-Nohelia; Pinedo-Cancino, Viviana-Vanessa; Ramal-Asayag, Cesar; Górgolas-Hernández-Mora, Miguel; Casapía-Morales, Martin (Frontiers in Veterinary Science, 2020)
Aims: to assess the prevalence of Chagas disease in pregnant women in Iquitos City, Peru. Material and Methods: cross-sectional survey in 300 pregnant women in Iquitos (Peru) from 1 May 2019 to 15 June 2019. Women were tested using an ELISA serology test. Results: serology was positive in one case (prevalence: 0.33%; 95% confidence interval: 7.1% to 13.9%), of a 25-year-old woman who lived in a wooden house with a leaf roof in a periurban area of Iquitos. She was familiar with kissing bugs and had chronic, asymptomatic Chagas disease. Conclusion: the prevalence of Chagas disease is low in the urban and peri-urban area of the city of Iquitos.